SOIL BEARING CAPACITY OF SHALLOW FOUNDATION BASED ON TERZAGHI METHOD IN CIPATAT, WEST BANDUNG, WEST JAVA - Wicaksana, Kintan Adelia Arum; Zakaria, Zufialdi; Muslim, Dicky; Khoirullah, Nur (Faculty of Geological Engineering, Universitas Padjadjaran, 2020)
Infrastructure development is a common thing that happened in Indonesia, especially house construction that happened in Cipatat, West Bandung, West Java. One of the important things in construction is a foundation and one of the foundation’s types is a shallow foundation. Soil bearing capacity is one of several things that used to calculate foundation planning. This research is using the Terzaghi method for soil bearing capacity. The data was obtained by taking the disturbed sample from three different locations. Those samples were tested in a laboratory, the test is a direct shear test to know about soil bearing capacity's value. The result is soil bearing capacity value range between 5.47 ton/m2 - 26.52 ton/m2. That value for soil bearing capacity is categorized as low.